Negotiating Outcome-Based Education in Indonesian Islamic Higher Education: Aligning Competency and Faith - Muhammad Nasir; Norimune Kawai; Muhammad Khairul Rijal; Muhammad Azwar Paramma (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
Outcome-Based Education (OBE) has been widely adopted to strengthen curriculum alignment, accountability, and graduate competencies. In the context of Islamic higher education (IHE), however, its implementation raises critical challenges in harmonizing competency-based learning outcomes with Islamic ethical and spiritual values. This study aims to explore how Indonesian IHE institutions interpret, negotiate, and implement OBE within their institutional contexts. This research employs a qualitative case study design. Data were collected through semi-structured interviews and document analysis involving 11 academic leaders and lecturers from eight IHE institutions. The findings reveal diverse interpretations of learning outcomes, tensions between national accreditation standards and Islamic educational principles, varying levels of lecturer readiness for student-centered learning, and unequal access to digital infrastructure. To address these challenges, institutions adopted strategies such as backward curriculum design, continuous quality assurance, integration of Islamic values into learning outcomes, enhancement of digital competencies, and partnerships with industry and community stakeholders. The study concludes that effective OBE implementation in IHE requires a contextualized and integrative approach. The implications highlight the need for curriculum models that embed Islamic values, strengthen lecturer professionalism, and supportive policy frameworks to advance the quality of Islamic education.